Pengaruh Capital Adequacy Ratio (CAR) dan Net Interest Margin (NIM) Terhadap Return On Asset (ROA) dan Non Performing Loan (NPL) Sebagai Variabel Intervening Pada PT Bank Pembangunan Daerah Kalimantan Selatan - Novita Dewi; Saladin Ghalib (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
This research aims to examine the influence of Capital Education Ratio (CAR), Non-Performing Loans (NPL), and Net Interest Margin (NIM) on Return on Assets (ROA) at PT Bank Pembangunan Daerah Kalimantan Selatan either partially or simultaneously. The sample in this research is the financial report of PT Bank Pembangunan Daerah Kalimantan Selatan for the 2015-2022 period. Data collection uses financial reports while data analysis uses Multiple Linear Regression Analysis via the SPSS version 23 program. The test results prove that the Capital Education Ratio (CAR) has an insignificant effect on Return on Assets (ROA), Non Performing Loans (NPL) has a significant effect on Return on Assets (ROA), an insignificant effect on Return on Assets (ROA), while simultaneously Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Net Interest Margin (NIM) have an influence on Return on Assets (ROA) at PT Bank Pembangunan Daerah Kalimantan Selatan